Fraction of exhaled nitric oxide is associated with disease burden in the German Asthma Net severe asthma cohort - Bal, Christina; Idzko, Marco; Škrgat, Sabina; Koch, Andrea; Milger, Katrin; Schulz, Christian; Zehetmayer, Sonja; Hamelmann, Eckard; Buhl, Roland; Korn, Stephanie (The European respiratory journal, 2022)
Tweetable abstract ERSpublications - click to tweetIn a severe asthma cohort of 1007 patients, high FENO was associated with chronic rhinosinusitis/polyps, later asthma onset, poor lung function and asthma control, low quality of life, frequent exacerbations and the need for maintenance OCS. #GANregistry https://bit.ly/3sNrtIQ
Gesehen am 20.07.2022